Influence of subcritical crack growth on the determination of fracture toughness in brittle materials. Issue 5 (April 2016) - Krautgasser, C.; Chlup, Z.; Supancic, P.; Danzer, R.; Bermejo, R.
Abstract: The strength of materials suffering from subcritical crack growth (SCCG) can be affected by the loading conditions and environment. This crack growth can also occur during the measurement of the material's fracture toughness, K Ic, yielding lower measured (apparent) values. In this work the K Ic measurements of two different brittle materials was compared in different environments ( i.e., water, ambient air and argon) using three testing methods: (i) Single Edge V-Notch Beam, (ii) Chevron Notch Beam, and (iii) Ball-on-three-Balls-KIc. A strong effect of the environment was found on the measured K Ic values using all three methods. Low " K Ic values" were measured in water, i.e., ∼1.3–1.7 MPa m 1/2 depending on the material, whereas higher "toughness values" were obtained in argon, i.e., ∼2.0–2.3 MPa m 1/2 . This is explained with a model accounting for the SCCG during the fracture toughness experiment. Recommendations on the assessment of fracture toughness in brittle materials are given.